Does the Depth of Gastric Ulceration Influence a Modified Dual Therapy with Amoxicilin and Lansoprazole for Helicobacter pylori-Positive Gastric Ulcer?. (1st October 2000) - Okai, Takashi; Ohtsubo, Koushiro; Sakai, Junta; Watanabe, Hiroyuki; Motoo, Yoshiharu; Kawashima, Atsuhiro; Norio, Sawabu
Abstract : PURPOSE: To clarify whether the depth of ulceration evaluated by endoscopic ultrasonography (EUS) influences a modified dual therapy with amoxicillin and lansoprazole for the treatment of Helicobacter pylori -positive patients with gastric ulcer. PATIENTS AND METHODS: Twenty-two consecutive cases of gastric ulcer (nine superficial ulcers and 13 deep ulcers) in H pylori -positive patients were studied. Ten of 22 patients received a two-week eradication therapy with amoxicillin 1500 mg/day, lansoprazole 30 mg/day and a new antiulcer agent with features in common with sucralfate, ecabet sodium, 2.0 g/day. They continued to receive the same doses of lansoprazole and ecabet sodium for the next six weeks. The other 12 patients received the same therapy except for those who underwent the four-week amoxicillin treatment. All patients underwent EUS both at the start of the study and eight weeks later. They then received ecabet sodium alone for the next six months as a maintenance therapy, followed by a six-month interval with no treatment. The final endoscopy was done one year after H pylori eradication therapy was completed to evaluate H pylori status and ulcer recurrence. RESULTS: The rates of endoscopic healing and H pylori eradication in the nine patients with superficial ulcer were 100%, irrespective of the period of amoxicillin treatment. In contrast, the rates of endoscopic evidence of healing and H pylori eradication in the 13 patients with deep ulcer were different for each period of amoxicillin treatment; that is, the rates of reduction in ulcer determined by echo and H pylori eradication in the four patients treated with the two-week amoxicillin course were significantly lower (P=0.03) than those in the nine patients treated with the four-week course. CONCLUSION: Ulcer depth is likely to influence the success of amoxicillin treatment for H pylori -positive patients with gastric ulcer.